HUBUNGAN KETAHANAN PANGAN KELUARGA DAN POLA KONSUMSI DENGAN STATUS GIZI BALITA KELUARGA PETANI (Studi di Desa Jurug Kabupaten Boyolali Tahun 2017) - Safitri, Adelia Marista; Pangestuti, Dina Rahayuning; Aruben, Ronny (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
The condition of family food security is influenced by the ability of the family to fulfill their food needs and result in the lack of nutritional fulfillment of family members, including toddlers. This type of research is analytical research using cross sectional approach. The population and the sample in this study were 43 toddlers aged 24-59 months selected with purposive sampling method. Data were analyzed using Pearson and Rank Spearman trials. The results of this study indicate most (65,1%) family food security in the category of not food resistant. The average food diversity score was 4,86 with moderate category (67,4%). The level of energy consumption was less than 48,8% and level of protein consumption was excessive (53,5%). Nutritional status of children under five by BB/TB was mostly (86%) normal, BB/U was in good nutrition (86%), and TB/U was normal (81,4%). There were correlations of food security with the level of energy consumption (ρ=0,000), protein consumption’s level (ρ=0,048), BB/U (ρ =0,036), and TB/U (ρ=0,010); level of energy consumption with BB/TB (ρ=0,006); levels of protein consumption with TB/U (ρ=0,005). There were no correlations between food type diversity with energy (ρ=0,129) and protein (ρ=0,376) consumption level; energy consumption level with BB/U (ρ=0,785) and TB/U (ρ=0,382); levels of protein consumption with BB/TB (ρ=0,091) and BB/U (ρ=0,240); food security with BB/TB (ρ=0,324). It was suggested for the children under five’s family to utilize the soil with garden plants or to raise livestock to fulfill households needs while also improving socio-economy so that nutritional needs can be fulfilled.